Peri-procedure efficacy and safety of one-stop hybrid surgery for the treatment of brain arteriovenous malformations: A single-center preliminary experience - Fang, Wei; Yang, Zijian; Liu, Yufeng; Yu, Jia; Sun, Peng; Zhao, Zhenwei; He, Yue; Zhang, Tao; Deng, Jianping (Frontiers in Neurology, 2022)
Abstract Background: Some deficiencies and shortcomings in treatment strategies of brain arteriovenous malformation (bAVM) remain. It is worth exploring whether the one-stop hybrid surgical platform can play a positive role in the treatment of bAVM. Objective: This study investigated short clinical and angiographic results of one-stop hybrid surgery for the treatment of bAVM. Methods: All patients with bAVM treated with one-stop hybrid surgery were reviewed from February 2017 to December 2021. Data including demographic information, clinical conditions, characteristics of AVM, procedure details, and clinical and angiographic results were collected. Result: In total, 150 cerebral bAVM patients received one-stop hybrid surgery; among them, 122 received surgical resection assisted by intraoperative DSA, and 28 were treated with combination surgical resection and endovascular embolization. Complete angiographic obliteration of the AVM was achieved in 136 patients (90.7%), and procedure-related death and neurological deficit rates were 7.3%. Of all relevant variables, logistic regression analysis showed that the Spetzler & Martin (S&M) score was the only factor related to the cure rate (P<0.001) and endpoint complication rate (P=0.007). Conclusions: In our preliminary experience, one-stop hybrid surgery for the treatment of brain AVMs achieves a high angiographic total occlusion rate, with acceptable peri-procedure morbidity and mortality. For S&M 4 and 5 lesions, more cases and further study are needed to investigate the effects and safety of hybrid surgery.